Psychological capital and safety in Global North-South cooperation : A field analysis of collaborative investigative journalism across the U.S.-Mexico border - Cheas, Kirsi (SAGE Publications, 2024)
This article builds on a field theoretical analysis of collaborative investigative journalism across the U.S-Mexico (Global North-South) border. The article examines contents produced in investigative collaboration between Salvadoran, Guatemalan, Mexican, and U.S. journalists, exposing human rights violations, crime, and corruption. The article elaborates on the concept of psychological capital and argues for its relevance in the study of cross-border collaborative investigative journalism. A key finding resulting from this research is that in most collaborative projects, psychological and other capital of the Central American and Mexican journalists was outweighed by the capital of the U.S. journalists. The psychological, social, and cultural capital of the Southern journalistic fields were highly relevant for the successful implementation of the examined projects, but not explicitly recognized in most reporting. The article also suggests the Southern journalists did not feel safe enough to suggest critical perspectives challenging the position of their Northern partners, who funded and supervised the collaborations. However, three projects, in which Northern and Southern journalists worked in Central America and Mexico side by side, manifested exemplary solidarity and recognition of the psychological and other capital of the Southern fields. Hence, it seems that witnessing the dangers affecting the region’s journalists firsthand can enable Northern journalists to better understand and appreciate the circumstances in which their Southern partners are living and working, reflected in more genuine appreciation of their psychological, cultural, and social capital.
Keywords: Cross-border collaboration; ﬁeld theory; Global North; Global South; independent journalism; psychological capital; safety of journalists; investigative journalism; fi=Viestintätieteet|en=Communication Studies|